Rankings in professional men`s tennis: a rich but underutilized source of information - Reid, M.; Morgan, S.; Churchill T.; Bane, M. K. (Journal of Sports Sciences, 2014)
Success in professional tennis is measured, at least in part, by rankings. However, there is little quantitative evidence to inform stakeholders regarding what represents the typical ranking progress of top-ranked players. The objective of this study was therefore to compare the ranking trajectories of male players whom achieved peak professional rankings in the Top 250, 175, 100, 50, 20 and 10. The 11,396 birthdates and weekly professional rankings of all players between 27 August 1973 and 31 October 2011 were collated. The peak ranks for each athlete according to their both chronological age and number of years on tour were identified and athletes were categorised into one of six career-peak ranking bands. One-way analysis of variance tests confirmed distinctive ranking trajectories, which were most pronounced among Top 10 players. The rankings of these players were statistically distinguishable following players` second year on tour or by 17 years of age. The ranking signature of all Top 100 players emerged as significantly different to players that failed to enter the Top 100 by their fourth year on the tour. Indeed, the representation of ranking as a function of years on tour should be considered for use by tennis policy-makers in the future.